Semantic Evolution of Terms during COVID: (Prototype of Ministry of Health’s Tweets) - Al-Mutairi, Latifah Awwadhah (Journal of Arabic Language Sciences and Literature, 2023)
This research dealt with the semantic development of words during the Corona pandemic, on social networks (Twitter), with the aim of identifying the most widespread words, especially with regard to the tweets of the Saudi Ministry of Health, and identifying the extent of the significance of these words, or their decline. To achieve this, the researcher used the descriptive approach, using the content analysis tool, to analyze the collected tweets, which numbered (100) tweets, as she confined (20) words for this purpose; for their repeating in these tweets. The researcher discussed these terms in view of their origin in Arabic dictionaries. In the following, the most prominent findings of the study are presented:• The Arabic language, like a living organism, grows and develops to keep pace with the developments of the times.• The Corona pandemic has a positive aspect represented in enriching the Arabic language lexicon with many words.• Generating new words as a result of the Corona pandemic• Borrowing new words from foreign languages, especially English• Society accepts these new terms and uses them extensively
Keywords: semantic development; words; Corona pandemic; Saudi Ministry of Health